Analisis Kuantitatif Hidrokuinon pada Krim Pemutih di Kota X Menggunakan Spektrofotometri UV–Vis - Maria Istiqomah; Ratih Tyas Widara; Agung Permata; Marshela Anjani (Journal of Pharmaceutical and Health Research, 2023)
Whitening cream is a cosmetic product containing organic chemicals or other substances which are used to whiten the face or remove black spots on the skin. Whitening cream has many benefits for sufferers of skin disorders, namely being able to whiten and remove black marks. Meanwhile, the concept of beauty circulating in society is having white skin. This stigma makes people, especially teenagers, justify any means to get white skin. One way to beautify your skin is to use skin whitening and lightening products. The aim of this research was to determine hydroquinone levels in whitening cream in X City using UV–vis spectrophotometry. The method used in this research is quantitative using the UV–vis spectrophotometric method. The research results showed that all of the 15 samples tested were positive for containing hydroquinone with the highest percentage of hydroquinone found in S1, S5, and S10 with a percentage of 0.0581%; 0.062%; and 0.0501%. Meanwhile, samples with low percentages were in S4, S6, S7, and S12 with a percentage gain of 0.011%; 0.0134; 0.0103%; and 0.0105%. It can be concluded that the hydroquinone levels of the 15 whitening cream samples do not meet the requirements permitted by BPOM No. 23 of 2019, namely 0%.